2017
DOI: 10.18488/journal.1007/2017.7.7/1007.7.147.159
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relation between Indian market sentiments and stock market returns

Abstract: This paper aims to understand the relation between contemporaneous stock market returns and investor sentiments in Indian context. The analysis is done for daily data over a range of five years. Market measure proxies of investor sentiments including the market mood index and the volatility index are examined to explore their nature of association with the stock market returns. The results show that changes in sentiments have a higher explanatory power than sentiments at level when determining statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…This is an indication that investors are not always rational in Nigeria, and their irrational investment decision significantly influences stock trading in the country. This result agrees with studies that found significant positive relationship between investors' sentiment and stock performance among emerging and developing countries (Dalika &Yudhvir, 2015;Asian Naik & Padhi, 2016;Alajekwu, Obialor, Okoro & Ibenta, 2017;Aggarwal, 2017;Pandey & Sehgal, 2019;Cheng, 2019). On the other hand, the finding from this study disagrees with studies that found no significant relationship between investors' sentiment and stock trading (Zainudin, Zaki, Hadi, Hussain & Kantakji, 2019).…”
Section: Conclusion and Recommendationssupporting
confidence: 71%
See 2 more Smart Citations
“…This is an indication that investors are not always rational in Nigeria, and their irrational investment decision significantly influences stock trading in the country. This result agrees with studies that found significant positive relationship between investors' sentiment and stock performance among emerging and developing countries (Dalika &Yudhvir, 2015;Asian Naik & Padhi, 2016;Alajekwu, Obialor, Okoro & Ibenta, 2017;Aggarwal, 2017;Pandey & Sehgal, 2019;Cheng, 2019). On the other hand, the finding from this study disagrees with studies that found no significant relationship between investors' sentiment and stock trading (Zainudin, Zaki, Hadi, Hussain & Kantakji, 2019).…”
Section: Conclusion and Recommendationssupporting
confidence: 71%
“…The birth of behavioural finance (otherwise behavioural economics) in the 1990s has been on the rise in empirical literature that has sought to determine whether stock trading is driven by investors' sentiments. There is a consensus in the literature that sentiment influences market performance among emerging markets (Dalika &Yudhvir, 2015;Naik &Padhi, 2016;Aggarwal, 2017;Pandey & Sehgal, 2019;Cheng, 2019). These studies corroborate findings from Alajekwu, Obialor, Okoro and Ibenta (2017) which found that sentiment significantly influences market performance in Nigeria.…”
Section: 0supporting
confidence: 67%
See 1 more Smart Citation
“…Pandey and Sehgal (2019) constructed the composite sentiment index for India and found that small firm effects are captured by the sentiment based factor. Aggarwal (2017) used MMI and volatility index to capture the sentiment in India. The study showed that MMI is positively related to stock returns and VIX is negatively related to stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…in the Indian stock market challenging the early works on financial asset price formation process, which states that noise traders are not important. And the existence of causal relationship between market return and sentiment and volatility and sentiment have been studied by Aggarwal (2017), Naik and Padhi (2016) and Kumari and Mahakud (2015, 2016) at the Indian financial market. All these factors motivate the present study, that is, to examine whether the performance of options trading can be improved if volatility forecasting incorporating investors’ sentiment was incorporated in the decision-making process at the Indian options market.…”
Section: Introductionmentioning
confidence: 99%